Comparative study of treatment for distal radius fractures with two different palmar locking plates. (June 2016) - Tanaka, H.; Hatta, T.; Sasajima, K.; Itoi, E.; Aizawa, T.
Few randomized trials have shown how the placement of a palmar locking plate affects outcomes. The purpose of this study was to compare clinical and radiological outcomes of fixation using locking plates with different concepts for placement relative to the watershed line in a prospective randomized trial. Sixty-four patients with a displaced distal radius fracture were divided into two groups according to the plates used for fixation: distal-type (AcuLoc TM, Group A) and proximal-type (VariAx TM, Group V). Wrist function including the range of motion and grip strength was compared at 1, 2, 3 and 6 months postoperatively. Loss of reduction was assessed radiologically. Both groups demonstrated overall satisfactory function at 6 months with no significant difference found between the groups. Minimal loss of reduction was demonstrated in both groups. Internal fixation using the palmar locking plates with two different placements provided satisfactory outcomes at 6-month follow-up, but our results indicate that plates placed distal to the watershed line may delay recovery of wrist motion.